LCA and Exergo-Environmental Evaluation of a Combined Heat and Power Double-Flash Geothermal Power Plant - Vitantonio Colucci (Sustainability, 2021)
This study deals with the life cycle assessment (LCA) and an exergo-environmental analysis (EEvA) of the geothermal Power Plant of Hellisheiði (Iceland), a combined heat and power double flash plant, with an installed power of 303.3 MW for electricity and 133 MW for hot water. LCA approach is used to evaluate and analyse the environmental performance at the power plant global level. A more in-depth study is developed, at the power plant components level, through EEvA. The analysis employs existing published data with a realignment of the inventory to the latest data resource and compares the life cycle impacts of three methods (ILCD 2011 Midpoint, ReCiPe 2016 Midpoint-Endpoint, and CML-IA Baseline) for two different scenarios. In scenario 1, any emission abatement system is considered. In scenario 2, re-injection of CO2 and H2S is accounted for. The analysis identifies some major hot spots for the environmental power plant impacts, like acidification, particulate matter formation, ecosystem, and human toxicity, mainly caused by some specific sources. Finally, an exergo-environmental analysis allows indicating the wells as significant contributors of the environmental impact rate associated with the construction, Operation & Maintenance, and end of life stages and the HP condenser as the component with the highest environmental cost rate.